Strain field reconstruction and damage identification in masonry walls under in-plane loading using dense sensor networks of smart bricks: Experiments and simulations. (15th July 2021) - Meoni, A.; D'Alessandro, A.; Kruse, R.; De Lorenzis, L.; Ubertini, F.
Graphical abstract: Highlights: Smart bricks are suited for strain monitoring and damage identification. Strain gauges and FE simulation prove the consistency of smart bricks' outputs. Smart bricks allow accurate reconstruction of the strain field. Smart bricks outperform strain gauges for damage detection and localization. Abstract: Cracks developing within a masonry structure induce changes in its strain field that can be measured for damage identification purposes through the adoption of strain-based structural health monitoring techniques. "Smart bricks" are strain-sensing piezoresistive clay bricks that can be used for this purpose. Along these lines, the paper investigates their use for strain field reconstruction and damage identification in masonry walls subjected to in-plane compressive loading. Experiments are first carried out to select the smart brick formulation and to demonstrate its effectiveness in estimating strain in compression. Then, an application of a network of smart bricks for monitoring a masonry wall eccentrically loaded in its plane is presented. Strains measured by the embedded smart bricks are benchmarked against those provided by strain gauges and further interpreted by means of a non-linear 3D model discretized with the finite element method. The strain field of the monitored structural element is reconstructed by spatially interpolating the strain measurements from smart bricks with a Kriging-based approach, while damage identification is achieved by defining a specific strain-based damage identifying feature. The obtained results clearly demonstrate that smart bricks significantly outperform strain gauges for strain field reconstruction and damage identification in masonry structures.